2021
DOI: 10.13189/saj.2021.090113
|View full text |Cite
|
Sign up to set email alerts
|

A Variation of Push Up for Overhead Pass on Volleyball Games

Abstract: This study aims to determine the effect of various push up exercises on the results of passing over in extracurricular volleyball activities for male students of class VIII Muhammadiyah Junior High School Megang Sakti, Musi Rawas. This type of research is a quasy experiment with a pretest-posttest one group design. The sample in this study amounted to 30 people. The instrument used was a passing test on the wall. The treatment in this study was in the form of various push-up training methods, after being given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This exercise can improve the ability of the arm muscles. The results showed that push-up training was appropriate for improving the basic technical skills of playing volleyball [7]. Observations on the accuracy of Smash in the volleyball game of Sigma Palu club on the ability to play volleyball have not been maximal.…”
Section: Introductionmentioning
confidence: 93%
“…This exercise can improve the ability of the arm muscles. The results showed that push-up training was appropriate for improving the basic technical skills of playing volleyball [7]. Observations on the accuracy of Smash in the volleyball game of Sigma Palu club on the ability to play volleyball have not been maximal.…”
Section: Introductionmentioning
confidence: 93%